PENINGKATAN BELAJAR MATEMATIKA MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD - Manik, Rotua (JURNAL PENA EDUKASI, 2019)
Abstract: Before the average category of action was carried out the student learning outcomes were in the low category with a completeness level of 0% (Of the 40 students in class X no students completed). In the first cycle after the action was carried out the student completeness rate was 7.69% (there were as many as 3 people). In the second cycle after further action was taken as a result of reflection in the first cycle the student's level of completion became 71.79% (completed as many as 29 people), activeness of students in following mathematics learning after action was taken both in cycle I and cycle II increased. In the first cycle the percentage of attendance was 92% and in the second cycle increased to 98%. Students in working on and collecting tasks are carried out on time, the more students express opinions in problem solving, the students work together independently. Keywords: Learn math, STAD Abstrak: Sebelum dilakukan tindakan kategori rata-rata hasil belajar siswa berada pada kategori rendah dengan tingkat ketuntasan 0 % (Dari 40 orang siswa di kelas X tidak ada siswa yang tuntas). Pada siklus I setelah dilakukan tindakan tingkat ketuntasan siswa 7,69 % (yang tuntas ada sebanyak 3 orang). Pada siklus II setelah dilaksanakan tindakan lebih lanjut sebagai hasil refleksi pada siklus I tingkat tuntasan siswa menjadi 71,79 % (tuntas sebanyak 29 orang), Keaktifan siswa dalam mengikuti pembelajaran matematika setelah dilakukan tindakan baik pada siklus I dan siklus II menjadi meningkat. Pada siklus I presentase kehadiran 92 % dan pada siklus II meningkat menjadi 98 %. Para siswa dalam mengerjakan dan mengumpulkan tugas-tugas dilakukan tepat waktu, semakin banyak siswa mengemukakan pendapat dalam pemecahan masalah, paara siswa bekerja secara bersama secara mandiri. Kata kunci: Belajar Matematika, STAD